Legal Surrogacy in question: Discussing with ChatGPT - Maestri, Enrico (Medicina Historica, 2023)
This paper is a faithful translation of a discussion between ChatGpt and the author on the ethical and legal implications of surrogacy. ChatGPT’s responses to my doubts or questions show that the OPEN AI chatbot tends to favour the method of accommodation. This is the hermeneutical method used by the High Courts to decide whether the legal rule or precedent to be applied in the case before them is constitutionally correct. ChatGPT prefers to consider controversial issues on the basis of “all things considered” rather than “all or nothing”. In this sense, ChatGPT can be seen as the computational realisation of Ronald Dworkin’s Judge Hercules.